2019
DOI: 10.1088/1748-9326/ab4031
|View full text |Cite
|
Sign up to set email alerts
|

Are global tropical cyclones moving slower in a warming climate?

Abstract: The local tropical-cyclone-related rainfall totals largely depend on the rain rate near the center and the translation speed of a tropical cyclone. Understanding how they respond to a changing climate has been a hot topic. A recent astounding study reported a 10% slowdown in global tropical-cyclone translation speed over the past 68 years and implicitly related this to the weakening of tropical circulation forced by the anthropogenic warming. It thereby suggested that it might result in more local rainfall to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 41 publications
0
22
1
Order By: Relevance
“…Furthermore, it was obvious that the TC translation speed over land also decreased before 1981, although there was no significant trend in the TC translation speed over land during the entire recording period. Chan found a significant speedup of global TC translation speed over land after 1970 [14], but here we showed that the TC translation speed over land in western North Pacific had no significant trend after 1981. Considering the mean TC translation speed is faster over land than over the ocean, any of the TC data inhomogeneity over land and the ocean may affect the trend in TC translation speed.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Furthermore, it was obvious that the TC translation speed over land also decreased before 1981, although there was no significant trend in the TC translation speed over land during the entire recording period. Chan found a significant speedup of global TC translation speed over land after 1970 [14], but here we showed that the TC translation speed over land in western North Pacific had no significant trend after 1981. Considering the mean TC translation speed is faster over land than over the ocean, any of the TC data inhomogeneity over land and the ocean may affect the trend in TC translation speed.…”
Section: Resultscontrasting
confidence: 69%
“…Chan also disagreed with Kossin and believed that the introduction of satellite capabilities since 1970s could influence that results to a great degree. Further, he even found a significant speedup of global TC translation speed over land after 1970 [14]. Therefore, it is still controversial about the slowdown trend in global TC translation speed.…”
Section: Introductionmentioning
confidence: 99%
“…Of the aforementioned projected impacts to hurricane characteristics, the parameters most likely to influence storm surge generation and therefore loading of petroleum infrastructure include changes to the forward translation speed (Gutmann et al, 2018;Kossin, 2018;Chan, 2019;Hall and Kossin, 2019;Lanzante, 2019;Moon et al, 2019;Hassanzadeh et al, 2020;Yamaguchi et al, 2020;Zhang et al, 2020), intensity (faster maximum winds), and hurricane size (radius to maximum wind speed) ( (Mudd et al, 2014a,b;Rosowsky et al, 2016;Gutmann et al, 2018)). The influence of climate change on the forward translation speed of tropical cyclones both at a global and basin-wide scale is uncertain as modeling studies have shown both an increase (Chan, 2019;Hassanzadeh et al, 2020;Yamaguchi et al, 2020) and decrease (Gutmann et al, 2018;Zhang et al, 2020) in the forward speed of simulated future tropical cyclones. Specifically for Texas, using outputs of climate models and downscaling experiments, Hassanzadeh et al (2020) found an increase in the northward steering winds and likelihood of faster-moving landfalling hurricanes under climate change.…”
Section: Hurricane Hazard Analysismentioning
confidence: 99%
“…Rosowsky et al (2016) also reported an increase in hurricane intensity along the U.S. East Coast under RCP 8.5. Findings from previous research on the effect of climate change on hurricane forward speed are more uncertain, predicting both an increase (Chan, 2019;Hassanzadeh et al, 2020;Yamaguchi et al, 2020) and decrease (Gutmann et al, 2018;Zhang et al, 2020) in the forward speed due to increased greenhouse gases. These climateinduced changes in hurricane characteristics will likely influence storm surge generation (Marsooli et al, 2019) and therefore loading on infrastructure in hurricane-prone regions (Done et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation